Oxygen Recovery Kinetics in the Forearm Flexors of Multiple Ability Groups of Rock Climbers. Issue 6 (June 2015) - Fryer, Simon M.; Stoner, Lee; Dickson, Tabitha G.; Draper, Steve B.; McCluskey, Michael J.; Hughes, Johnathan D.; How, Stephen C.; Draper, Nick
Abstract : Abstract: Fryer, SM, Stoner, L, Dickson, TG, Draper, SB, McCluskey, MJ, Hughes, JD, How, SC, and Draper, N. Oxygen recovery kinetics in the forearm flexors of multiple ability groups of rock climbers. J Strength Cond Res 29(6): 1633–1639, 2015—The purpose of this study was to determine muscle tissue oxidative capacity and recovery in intermediate, advanced, and elite rock climbers. Forty-four male participants performed (a) sustained and (b) intermittent contractions at 40% of maximal volitional contraction (MVC) on a sport-specific fingerboard until volitional fatigue. Near-infrared spectroscopy was used to assess muscle tissue oxygenation during both the exercise and the 5-minutes passive recovery period, in the flexor digitorum profundus (FDP) and flexor carpi radialis (FCR). During the sustained contraction only, muscle tissue deoxygenation (O2 debt) in the FDP and FCR was significantly greater in elite climbers compared with the control, intermediate, and advanced groups (FDP: 32 vs. 15, 19, 22%; FCR: 19 vs. 11, 8, 15%, respectively). However, elite climbers had a significantly quicker time to half recovery (T1/2 ) than the control and intermediate groups in the FDP (8 vs. 95 and 47 seconds, respectively) and the FCR (7 vs. 30 and 97 seconds, respectively) because the O2 % recovered per second being significantly greater (FDP: 4.2 vs. 0.7 and 0.3; FCR: 4.8 vs. 0.1 and 0.2, respectively). Furthermore, during the intermittent contraction, T1/2 in elite climbers was significantly quicker compared with the control and intermediate groups in the FDP (8 vs. 93 and 83 seconds, respectively) and FCR (16 vs. 76 and 50 seconds, respectively). Consequently, lower-level climbers should focus training on specific intermittent fatigue protocols. Competition or elite climbers should make use of appropriate rests on route to aid recovery and increase the chances of reaching the next hold.